Perception of students of Service-Learning in Valencian rural schools: validation of an instrument - García Monteagudo, Diego (Revista Complutense de Educación, 2024)
In recent years, educational research has analyzed the factors that influence the generation of significant learning and the development of citizenship in rural schools. Among these factors, teacher training is a relevant element in the development of student learning, since there is no specific training to exercise the teaching profession in these schools. The objective of this study is to know the perception that primary school students (fifth and sixth grade) have about the didactic experiences of Service-Learning that they have experienced in the 2021-22 academic year in Grouped Rural Schools (GRS) of the Valencian Community. The research has a quantitative approach, with a non-experimental and cross-sectional design, with a descriptive-correlational range, which analyses the psychometric properties of an instrument to measure the perception of 420 students about the PHC applied in ten GRS in the Valencian Community. The instrument "Scale of Perception of Service Learning in Grouped Rural Schools (SPSSLGRS)", has been designed and validated with the aim of measuring the three dimensions of the service-learning in relation to the educational projects developed in ten GRS of the Valencian Community. The scale has shown excellent psychometric qualities, which ensures its validity and reliability. The results reveal that there is a moderate perception of Service Learning, with more significant differences by grades (fifth and sixth of primary education), which suggests further research in this type of school with other methodological approaches in the coming years.